Skull and mandible formation in the cuckoo (Aves, Cuculidae): Contributions to the nomenclature in avian osteology and systematics - Posso, Sérgio Roberto [UNESP]; Donatelli, Reginaldo José [UNESP] (Portico, 2005)
The study of the contributions of different bones to the formation of the skeleton in birds is necessary: (1) to establish homologies in comparative anatomy; (2) to delimit each bone structure correctly, mainly in relation to the skull and mandible where the bones are fused to each other in adults; and (3) to standardize nomenclature in avian osteology. In this paper at least one young specimen belonging to each sub-family of Cuculidae was examined in order to identify each bone in terms of boundaries and contributions to skull and mandible formation. These cuckoos specimens were also compared with adults and young of turacos and hoatzin. The results show little variation of skull and jaw among the young cuckoos studied compared with the variations among adult specimens. However, it provides new suggestions for the boundaries and nomenclature of certain osseous structures in the skull and mandible of birds, specifically fissura zona flexoria craniofacialis, prominetia frontoparietalis, crista temporalis transversa, processus squamosalis, fossa laterosphenoidalis, tuberculum laterosphenoidale and processus retroangularis. This study also provides more reliable homologies for use in cladistic analysis and above all it contributes to the phylogenetic position of Cuculidae within Neognathae, specifically the skull formation suggest that turacos and hoatzin are more similar to each other than either is to the cuckoos. © 2005 Taylor & Francis.
Keywords: Cuculidae; Homology; Nomenclature; Ontogeny; Osteology; bird; bone structure; mandible; nomenclature; nonhuman; ontogeny; ossification; phylogeny; priority journal; skull; Age Factors; Animals; Beak; Birds; Evolution; Mandible; Skull; Species Specificity; Terminology; Aves; Neognathae; Opisthocomus hoazin